The potential of meropenem and piperacillin-tazobactam combination to Acinetobacter spp clinical isolates in vitro - Alindya Diani; Eggi Arguni; Ludhang Pradipta Rizki (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2020)
Acinetobacter spp is one of the most common causes of nosocomial infection, especiallysepsis. A lot of antibiotics resistance happen related to Acinetobacter-related sepsis treatment. This study aimed to evaluate the potential of meropenem and piperacillin-tazobactam combination against Acinetobacter spp in in vitro by using paper strip test. This was experimental study conducted in September to December 2015 at Departement of Microbiology, Faculty of Medicine, Public health, and Nursing, Universitas Gadjah Mada, Yogyakarta, Indonesia. Clinical isolates of Acinetobacter samples were obtained from collections of the Department of Microbiology. The data were analyzed using post-test analysis which was conducted by observation over 24 h after the paper strip test was applied in bacterial culture. The MIC value of the antibiotic combination was recorded based on observation. The result showed 12 of 17 clinical isolates were synergistic potential (70.59%) and 5 others were indifferent potential (29.41%). Two of five clinical isolates that show indifferent potential were A. baumannii and all of the clinical isolates that show synergistic potential were Acinetobacter spp. It can be concluded that the combination of meropenem and piperacillin-tazobactam showed more synergistic dominantly than the single use of each of them.